Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues related to the economy of Poland. Thanks to its sound policies, close links to the German supply chain, and substantial EU transfers, Poland is the only country in the European Union that avoided an outright recession during the global financial crisis. However, this strong performance has masked enduring regional disparities, which are undermining the quality of growth. Poland faces significant long-term challenges as an aging population weighs on potential growth and public finances. The new government, which took office in November, has approved a Responsible Development Plan, focused on spurring growth through innovation and reducing social and regional disparities.